AB0607 Determinants of Unemployment amongst Australian Systemic Sclerosis Patients. (15th July 2016) - Morrisroe, K.; Huq, M.; Stevens, W.; Rabusa, C.; Proudman, S.; Nikpour, M.
Abstract : Background: The ability to work is a fundamental component of everyday life. Objectives: To assess employment status, risk factors for unemployment and the associations of unemployment with patients' health related quality of life (HRQoL). Methods: All patients completed in a systemic sclerosis (SSc) longitudinal cohort study, completed an employment questionnaire on enrolment. Clinical manifestations were defined based on presence at the time of enrolment. Summary statistics, chi-square tests, univariate and multivariable logistic regression were used to determine the associations of various risk factors with employment. Results: Among 1587 SSc patients, 160 (20%) were unemployed at the time of cohort enrolment excluding retired patients. Of these, 63% had limited disease subtype. Mean (±SD) age at enrollment was 51.9 (±10.4) years; 13 years below the average retirement age in Australia. Mean (±SD) disease duration at recruitment was 11.1 (±10.9) years. Multivariable regression analysis revealed the presence of digital amputation (OR 3.9, 95%CI 1.7–9.1, p=0.002), diffuse disease subtype (OR 2.2, 95%CI 1.3–3.5, p-value=0.002), sicca symptoms (OR 2.7, 95%CI 1.6–4.4, p<0.001), a physical job (OR 1.8, 95%CI 1.1–3.1, p=0.03) and pulmonary arterial hypertension (OR 2.2, 95%CI 1.1–4.5, p=0.02) to be associated with unemployment. Unemployed patients had consistently poorer HRQoL scores in all domains (physical, emotional and mental health) of the SF-36 form than those who were employed. Conclusions: SSc is associated with substantial work disability and unemployment, which is in turn associated with poor quality of life. Raising awareness, identifying modifiable risk factors and implementing employment strategies and work place modifications are possible ways of reducing this burden. Acknowledgement: This work was supported by Scleroderma Australia, Arthritis Australia, Actelion Australia, Bayer, CSL Biotherapies, GlaxoSmithKline Australia and Pfizer. Dr Morrisroe is a recipient of an NHMRC, RACP Shields Fellowship and an Australian Rheumatology Association (Vic) "top-op" PhD scholarship. Dr Nikpour holds a University of Melbourne Faculty of Medicine Dentistry and Health Science David Bickart Clinician Researcher Fellowship and is a recipient of an NHMRC Fellowship (APP1071735). Disclosure of Interest: None declared